2017
DOI: 10.1038/srep40719
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Mediated Regulation of Endoplasmic Reticulum-Associated Degradation and its Effects on Prostate Cancer

Abstract: The endoplasmic reticulum (ER) comprises thirty percent of the newly translated proteins in eukaryotic cells. The quality control mechanism within the ER distinguishes between properly and improperly folded proteins and ensures that unwanted proteins are retained in the ER and subsequently degraded through ER-associated degradation (ERAD). Besides cleaning of misfolded proteins ERAD is also important for physiological processes by regulating the abundance of normal proteins of the ER. Thus it is important to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 43 publications
2
56
0
4
Order By: Relevance
“…AR levels in 22RV1 and LNCaP cells are similar (Erzurumlu and Ballar, 2017), while LNCaP-ARhi and VCaP cells overexpress AR compared to LNCaP (or LNCaP-pcDNA3.1) with VCaP showing the highest levels of AR (Urbanucci et al, 2012; Waltering et al, 2009). VCaP cells were indeed the most sensitive cells to JQ1 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…AR levels in 22RV1 and LNCaP cells are similar (Erzurumlu and Ballar, 2017), while LNCaP-ARhi and VCaP cells overexpress AR compared to LNCaP (or LNCaP-pcDNA3.1) with VCaP showing the highest levels of AR (Urbanucci et al, 2012; Waltering et al, 2009). VCaP cells were indeed the most sensitive cells to JQ1 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Another critical proteostatic pathway is ER-associated degradation (ERAD), which, with a few exceptions (Erzurumlu and Ballar, 2017;Singh et al, 2015), has not been measured in tumor-derived cells. ERAD reduces ER stress by identifying and destroying misfolded, improperly processed and orphaned subunits of oligomeric proteins for proteasome-mediated degradation (Haas et al, 1982;Olzmann et al, 2013;Raasi and Wolf, 2007;Vembar and Brodsky, 2008;Ye et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…ERAD malfunction or insufficiency leads to ER stress and activation of the unfolded protein response (UPR) . Several factors of ERAD machinery are upregulated in PCa, and UPR activation in PCa has been recently demonstrated, providing a possible vulnerability exploitable therapeutically . We have recently shown that DSF targets cancer via inhibition of the p97/NPL4 pathway, essential for ERAD .…”
Section: Resultsmentioning
confidence: 99%